Outcomes of Dialysis in low Income Country – An Experience in a Tertiary Care Center of Bangladesh (Bangladesh Journal of Medicine, 2021)
Background: The widespread use of hemodialysis to prolong life of end-stage renal disease (ESRD) patients has been a remarkable achievement, preventing death from uremia in these patients. The aim of the study was to find out the outcomes of haemodialysis patients with end-stage renal disease (ESRD) in low Income County.Methods: A hospital based prospective observational study was performed in the of Department of Nephrology, Shaheed Suhrawardy Medical College. Total 189 patients who stated dialysis during study period were included. All patients were monthly followed up and appropriate investigation done. All data recorded in a case record form. Study protocol approved by Ethical committeeof institute. Data analyzed in SPSS software version 25.Results: Among 189 ESRD patients on MHD selected with mean age 49.16 years (15-82), male was 60.3% and female 39.7%.Eighty eight 46.5% patient died and 39.15%(74) patient discontinue dialysis due to lack of financial support or helping assistant or social support. Three (1.6%) patients underwent renal transplantation and five patients (2.6%) transfer to other dialysis center. Average life span in dialysis 256 day (16-786 days). Most of the paints was on twice weekly dialysis 84%. Vascular access of stating dialysis was 73.8% by catheter and only 32.2% stated with AV fistula.Conclusion: A large group of patients leave dialysis due to financial or helping personal or social supportwithin 3-4 months of stating dialysis. A significant number of patients died due to multiple risk factors within 8-9 months. Identification of risk factors for early mortalityis essential and appropriatemeasure should take to prevent discontinuation at community and national level.Bangladesh J Medicine July 2022; 33(1) : 52-56